Growth of (Na0.5Bi0.5)TiO3-SrTiO3 single crystals by solid state crystal growth. Issue 16 (December 2016) - Lee, Daeki; Vu, Hung; Sun, Hengyang; Pham, Thuy Linh; Nguyen, Dang Thanh; Lee, Jong-Sook; Fisher, John G.
Abstract: Single crystals of 0.8(Na0.5 Bi0.5 )TiO3 -0.2SrTiO3 were grown for the first time by the Solid State Crystal Growth technique (SSCG). [001], [110] and [111]-oriented seed crystals of SrTiO3 were buried in 0.8(Na0.5 Bi0.5 )TiO3 -0.2SrTiO3 powder which was then pressed to form samples. Samples were sintered at 1200 °C for 20 h and single crystals of 0.8(Na0.5 Bi0.5 )TiO3 - 0.2SrTiO3 grew on the seeds. The direction of least growth was [001] (∼60 µm), with the [110] and [111] directions having growth distances of ∼200 µm. Chemical composition of the crystals was analyzed by Electron Probe Micro Analysis and found to be close to the nominal composition, with some volatilization of Na and Bi. Micro-Raman scattering showed that the single crystal has the (Na0.5 Bi0.5 )TiO3 structure. In order to measure the electrical properties, a single crystalline thick film of 0.8(Na0.5 Bi0.5 )TiO3 -0.2SrTiO3 was grown on a [001]-oriented Nb-doped SrTiO3 seed crystal. The single crystalline thick film showed relaxor-like relative permittivity vs. temperature behavior and polarization – electric field hysteresis loops for a lossy ferroelectric material.